The Role of Short Videos on Tiktok Social Media on Individual Loyalty In Online Skincare Shopping - Anggraheni, Eva Shera; Kustiawan, Unggul (PINISI Discretion Review, 2023)
The quality of the content in short videos refers to a consumer's perception of the relevance, creativity and uniqueness of a content. This is an output of efforts to fulfill the expectations of content providers for consumers through interest. The widespread use of the Internet has changed the way customers expect to build relationships with sellers. In this study, data were collected using the survey method. In this observation, we examined the role and quality of content, quality of relationships or relationships, and attachment in ensuring customer loyalty in shopping through short videos on social media. If the increase in content quality can stimulate attachment in shopping through short videos on social media, which will positively be a factor influencing customer loyalty Respondents in this study are customers with shopping experiences through short videos on social media. outer loading value 0.7. So it can be concluded that all indicators are valid to proceed to further testing. So it can be concluded that all the variables contained in the research model, which means they have fulfilled the requirements. Composite reliability is one of the tests used to test the reliability value of variable indicators. The results of the study concluded that there is a positive influence between the Content Quality variable on Relationship Quality. The quality of content on social media can affect the quality of the bond with the seller. The Customer Perceived Value variable has a positive effect on Relationship Quality. Customer ratings can affect the quality of the relationship between customers and buyers. Content Quality variable has a positive effect on Stickiness. Relationship Quality variable has a positive effect on Stickiness. Stickiness variable has a positive effect on Behavior Loyalty.